906 Implementing and Re-Designing A Virtual Fracture Clinic (VFC) During The COVID-19 Pandemic. (4th May 2021) - Erotocritou, M; Overton, A; Ang, W W; Walker, M; Burns, S; Berber, O
Abstract: Introduction: We have implemented a VFC model during the COVID-19 pandemic to minimise the number of face-to-face consultations and the risk of transmission. Method: The VFC was implemented and assessed using 3 PDSA cycles. Initially, a paper referral system was introduced along with treatment pathways. Subsequently an electronic referral system was established. The 3 rd PDSA cycle involved training A&E staff on referrals and treatment pathways. At each stage the number of VFC referrals and clinic follow-ups were measured. Patient satisfaction was assessed using a telephone survey with a random sample of 30 patients. Results: There was a statistically significant reduction in face-to-face follow-ups between pre-VFC (Total:4083, Average:86.87) and post-VFC (Total:713, Average:35.65) p-value<0.0001. There was a statistically significant increase in patient satisfaction after the implementation of the electronic referral system and staff re-training(9.25) compared to paper referrals(8.23), p-value=0.02064. Conclusions: Our study demonstrated that the VFC successfully reduced the number of face-to-face follow-ups while maintaining patient satisfaction. Thus, it is an effective alternative to conventional fracture clinics. A similar model can be introduced at other hospitals to minimise in-person consultations and risk of transmission, while standardising patient care. It has also highlighted the importance of appropriate technological infrastructure, staff training and service evaluation.